2022
DOI: 10.3390/jcm11237180
|View full text |Cite
|
Sign up to set email alerts
|

Statins and the Risk of Gastric Cancer: A Systematic Review and Meta-Analysis

Abstract: Previous epidemiological studies have reported that the use of statins is associated with a decreased risk of gastric cancer, although the beneficial effects of statins on the reduction of gastric cancer remain unclear. Therefore, we conducted a systematic review and meta-analysis to investigate the association between the use of statins and the risk of gastric cancer. Electronic databases such as PubMed, EMBASE, Scopus, and Web of Science were searched between 1 January 2000 and 31 August 2022. Two authors us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…The above findings are in line with some of the epidemiological findings from outside China [5][6][7][8]. Moreover, several more in-depth studies have been carried out by some scholars.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The above findings are in line with some of the epidemiological findings from outside China [5][6][7][8]. Moreover, several more in-depth studies have been carried out by some scholars.…”
Section: Discussionsupporting
confidence: 88%
“…They are as follows: (1) Controls were selected according to a ratio of 1:2; (2) As there were significantly more men than women with GC, controls were required to match each group in terms of gender; (3) No previous malignancy of any type; (4) History of previous illnesses as well as medication history were clearly documented in the medical history of the examination; (5) Those who agree to participate in this study and sign the informed consent form.…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the impact of statins on human health is beyond simple LDL lowering, which is also named “statin pleiotropy” [ 26 , 27 ]. So far, statins exhibited anti-inflammatory effects and benefits in diseases related to inflammation: atherosclerosis [ 28 ], chronic heart failure [ 29 ], sepsis [ 30 ], COVID-19 [ 31 ], diabetic nephropathy [ 32 ], gastric cancer [ 33 , 34 ], Alzheimer’s diseases [ 35 ], bone disorders [ 36 ], and autoimmune diseases [ 37 ]. Meta-analysis of 15 randomized controlled trials provided evidence that lipophilic statins pose more pleiotropic effects compared to hydrophilic statins due to easier penetration into the cell membranes [ 38 ].…”
Section: Statinsmentioning
confidence: 99%
“…However, the preventative effects of medications such as statins, aspirin, metformin, and proton pump inhibitors (PPIs) against GC remain controversial. Additionally, several systematic reviews and metaanalyses investigated medication use and GC risk [16,17], but in fact, no attempts have been made to quantify the credibility of these findings. Given the uncertainty of observational research, this quantification of evidence is both timely and critical [18,19].…”
Section: Introductionmentioning
confidence: 99%